Manajemen Pembelajaran dalam Meningkatkan Prestasi Belajar Siswa di MTs Jam’iyah Mahmudiyah - Neliwati Neliwati; Isra Adawiyah Siregar; Lia Ariska Ritonga (Edumaspul: Jurnal Pendidikan, 2021)
This study aims to determine learning management in improving student achievement at MTs Jam'iyah Mahmudiyah. This research seeks to explain how learning management is and how student achievement is at MTs Jam'iyah Mahmudiyah. The method used in this research is qualitative. Data collection techniques using observation techniques, interviews and documentation study techniques to obtain valid data about learning management in improving student achievement. This research was conducted at MTs Jam'iyah Mahmudiyah which is located on Jl. Sheikh M. Yusuf, Tanjung Pura District. The results of the study show that the implementation of learning management in general is quite good, marked by planning that includes annual programs, semesters, syllabus, educational calendars, and lesson plans, in planning there are still flaws that are not good, because there are still many programs that have not been designed and made and learning achievement as a result achieved by students after experiencing a learning process within a certain period, student learning outcomes include the cognitive, affective and psychomotor domains. Student learning achievement at MTs Jam'iyah Mahmudiyah is quite good which is marked by: The value of several student lessons has met the KKM target, the application of religious practices has been carried out in the daily lives of students and students of MTs Jam'iyah Mahmudiyah have won competitions in events with good predicates.